Оцінка пріоритетності інноваційних проектів на підприємстві - Крамськой, Дмитро Юрійович; Нотовський, Павло Валентинович; Дягілєва, Олена Леонідівна (НТУ "ХПІ", 2015)
Запропоновано методичний підхід до оцінки пріоритетності інноваційних проектів на підприємстві, використання якої передбачає визначення типу нововведення, проведення експертних оцінок і використання методу евклідових відстаней. Елементи відстаней визначаються за допомогою експертних оцінок по виділених групах критеріїв якості інноваційного проекту. Зроблено висновки що найбільш істотними є такі групи як: політика підприємства; проект; НДДКР; фінанси та виробництво. Дана система критеріїв змінюється з урахуванням цілей підприємства, видів інновацій, інших внутрішніх і зовнішніх факторів.

The methodical approach for assessing the priority of innovative projects in the enterprise, the use of which provides the definition of the type of innovation, peer reviews and the use of Euclidean distances. Elements of the distances determined by expert assessments of selected groups of quality criteria of the innovative project. Comparative characteristics of innovation and investment projects showed that the Euclidean distance method is most appropriate to prioritize funding as product and technological innovation in a high degree of uncertainty and risk. The conclusions as to whether groups are the most significant: the policy of the enterprise; project; Research and development; finance and production. This set of criteria taking into account the changing goals of the company, types of innovation, other internal and external factors.
Evaluation prioritization of innovation projects in the enterprise
Keywords: стратегія; менеджмент; діяльність інноваційна; expert evaluation; strategy; management